2006
DOI: 10.1111/j.1365-4632.2006.02878.x
|View full text |Cite
|
Sign up to set email alerts
|

Pimecrolimus is effective in Fox–Fordyce disease

Abstract: Fox-Fordyce disease (FFD) or 'apocrine miliaria' is a rare benign skin condition characterized by obstruction of the apocrine sweat gland. Treatment is generally unsatisfactory. A 15-year-old girl presented with intensely pruritic lesions on her axillae, chest and groin. Histology from an axillary skin biopsy confirmed FFD. The patient was commenced on pimecrolimus cream twice daily for three months and then once daily for a further three months. After a month she had marked improvement of her symptoms. By thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Phototherapy or topical retinoids to exfoliate the surface have been tried. Pimecrolimus has been reported to be of help (Pock et al 2006). Surgical measures may be used as a last resort.…”
Section: Fox-fordyce Diseasementioning
confidence: 99%
“…Phototherapy or topical retinoids to exfoliate the surface have been tried. Pimecrolimus has been reported to be of help (Pock et al 2006). Surgical measures may be used as a last resort.…”
Section: Fox-fordyce Diseasementioning
confidence: 99%
“…Most recently, pimecrolimus was shown to be successful in 3 young females [6] . Other methods mentioned in the literature include adapalene gel [4] , liposuction-assisted curettage [7] , topical clindamycin [8] , oral retinoids [9] , topical tretinoin cream [10,11] , topical 5% benzoyl peroxide combined with loratadine [12] , ultraviolet radiation [13] and electrocoagulation [14] .…”
Section: Case Reportmentioning
confidence: 99%
“…Treatments include topical clindamycin, corticosteroids, tretinoin, benzoyl peroxide, oral isotretinoin, oral contraceptives, ultraviolet *Address correspondence to this author at the Department of Dermatology, Chelsea and Westminster Hospital, 369 Fulham Road, London, SW10 9NH, UK; E-mail: nilesh.morar@chelwest.nhs.uk light, electrocoagulation, copper vapour laser, and liposuction-associated curettage. To date, there has been one previous case report demonstrating a successful response to eight weeks of pimecrolimus in three female patients after unsuccessful treatment with topical corticosteroids and tretinoin [3].…”
mentioning
confidence: 99%
“…Pharmacokinetic studies of pimecrolimus have demonstrated negligible systemic absorption following topical application [3]. Side effects of topical corticosteroids are not seen with pimecrolimus.…”
mentioning
confidence: 99%